Novel cases of amyotrophic lateral sclerosis after treatment of cerebral arteriovenous malformations (Swiss Medical Weekly, 2016)
Previous case studies reported nine patients with cerebral arteriovenous malformations (AVM) who developed amyotrophic lateral sclerosis (ALS) after AVM embolisation. Here, we describe three novel cases of ALS which developed 13–34 years after treatment, including embolisation, of cerebral AVM. This study provides further arguments supporting the thesis that embolisation of cerebral AVM might influence the risk of later ALS development.